Al-Islām wa al-qānūn wa al-dawlah: Dirāsah fī fikri Ki Bagus Hadikusumo wa dawrihi - Hakim, Sudarnoto Abdul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
This article discusses the intellectual and political biography of Ki Bagus Hadikusumo, a prominent Muslim leader in Indonesia. He was born in Yogyakarta where he grew up in a Muslim priyayi family of Kauman in the city. This study explains that the Sufi tradition of Pesantren Wonokromo in Yogyakarta deeply influenced his religious thoughts. Later, he was noted as one of the first students of K.H. Ahmad Dahlan, the founder of Muhammadiyah. It is clear that he was under a strong intellectual, ideological and religious influence of Dahlan. He published works on Islamic theology, Fiqh, Sufism, and also on Islam and state. During the Japanese occupation, he became the Chairman of Muhammadiyah organization . Ki Bagus was also known as a prominent leader of political parties, i.e. PII, MIAI, Masyumi and then a prominent member of BPUPKI, an important element of Indonesian independence in 1945. Representing a nationalist-Islamist wing, he greatly contributed to the politics of early modern Indonesia by (1) preparing the Indonesian constitution, and (2) providing solid arguments for Muslims to accept Pancasila as the nation’s state ideology.DOI: 10.15408/sdi.v21i1.881